The Impact of Corporate Governance, Company Size, and Company Age Towards Financial Performances and Company Value (in Indonesia Manufacturing Companies Listed in IDX) - Christian Andi Winarto; Steven Anderson (iBuss Management, 2019)
Public awareness and relevancy of corporate governance have increased significantly given the corporate bribery and fraud as part of agency cost in the last 20 years. However, the number of research studying corporate governance direct effect towards financial performance and company value in Indonesia are lacking. In this research, the researcher intention is to find the effect of corporate governance towards financial performance and company value with company size and company age as control variables of Indonesian manufacturing companies listed in IDX. In this research, financial performance will be measured using Return on Equity while company value will be measured using Tobin’s Q. Corporate governance will be measured using the corporate governance mechanism (Haat, Rahman, and Mahenthiran, 2008) which involves proportion of independent director, quality of director, insider ownership, foreign ownership, debt to asset, and audit quality. The research data collection is done by gathering data from 63 manufacturing companies listed in IDX that has passed the purposive sampling criteria and analyzed using multiple linear regression. The result of this research concludes that corporate governance have no significant effect towards financial performance while debt to asset, and audit quality are found to have significant impact towards company value. Keywords: Corporate Governance, Company Size, Company Age, Return on Equity (ROE), Company Value (Tobin’s Q)